Light drinking versus abstinence in pregnancy – behavioural and cognitive outcomes in 7‐year‐old children: a longitudinal cohort study. Issue 11 (17th April 2013) - Kelly, Y; Iacovou, M; Quigley, MA; Gray, R; Wolke, D; Kelly, J; Sacker, A
Abstract : Objective: To assess whether light drinking in pregnancy is linked to unfavourable developmental outcomes in children. Design: Prospective population‐based cohort. Setting: UK. Population: Ten thousand five hundred and thirty‐four 7‐year‐olds. Methods: Quasi‐experimental using propensity score matching (PSM) to compare children born to light (up to 2 units per week) and non‐drinkers. Main outcome measures: Behavioural difficulties rated by parents and teachers; cognitive test scores for reading, maths and spatial skills. Results: Ordinary least squares (OLS) regression and PSM analyses are presented. For behavioural difficulties, unadjusted estimates for percentage standard deviation (SD) score differences ranged from 2 to 14%. On adjustment for potential confounders, differences were attenuated, with a loss of statistical significance, except for teacher‐rated boys' difficulties. For boys, parent‐rated behavioural difficulties: unadjusted, −11.5; OLS, −4.3; PSM, −6.8; teacher‐rated behavioural difficulties: unadjusted, −13.9; OLS, −9.6; PSM, −10.8. For girls, parent‐rated behavioural difficulties: unadjusted, −9.6; OLS, −2.9; PSM, −4.5; teacher‐rated behavioural difficulties: unadjusted, −2.4; OLS, 4.9; PSM, 3.9. For cognitive test scores, unadjusted estimates for differences ranged between 12 and 21% of an SD score for reading, maths and spatial skills. After adjustment for potential confounders, estimates were reduced, but remained statistically significantly different for reading and for spatial skills in boys. For boys, reading: unadjusted, 20.9; OLS, 8.3; PSM, 7.3; maths: unadjusted, 14.7; OLS, 5.0; PSM, 6.5; spatial skills: unadjusted, 16.2; OLS, 7.6; PSM, 8.1. For girls, reading: unadjusted, 11.6; OLS, −0.3; PSM, −0.5; maths: unadjusted, 12.9; OLS, 4.3; PSM, 3.9; spatial skills: unadjusted, 16.2; OLS, 7.7; PSM, 6.4. Conclusion: The findings suggest that light drinking during pregnancy is not linked to developmental problems in mid‐childhood. These findings support current UK Department of Health guidelines on drinking during pregnancy.